Compilation of Design Guideline for Piled Raft Foundation - Abdul Rahman, Nur Hayati (Universiti Teknologi Petronas, 2008)
Piled raft foundation is being used widely nowadays, due to its advantages in foundation construction. Piled raft can be used for different cases, such as settlement reducers, and improving bearing capacity of shallow foundation. Piled raft foundation is one of the complex foundation, because it has to consider varies of aspects and consideration. In UTP, especially for civil engineering students, this guideline will help them to learn about piled raft foundation. In this project, one design guidelines will be compiled to help students and others user, in learning the piled raft design. The design guideline will focus on the used of piled raft as settlement reducer for development on soft soil area, where friction pile is used in the design and it will be a "floating" piled raft. In others words, the pile group are not driven until reached the hard layer, but its length will cut at certain depth. Simple calculation methods introduced by various researchers are used in the design calculation, such as Randolph, Poulos and etc. The guideline coverage is ranging from the early staged of soil investigation until design analysis. All the information are collected from the available guideline produced by other parties such as geotechnical consultant, reference books, journals and articles. At the end of this project, one compilation of piled raft design will be documented and together with a spreadsheet, with the objective to assist students in design calculation.